Novel preclinical method for evaluating the efficacy of a percutaneous treatment in human ex vivo calcified plaque. - Chisena, Robert S.; Sengenberger, Jordan; Shih, Albert J.; Gurm, Hitinder (Medical & Biological Engineering & Computing, 2021)
The lack of suitable atherosclerotic calcification models and testing strategies inhibits preclinical efficacy testing of existing and novel percutaneous devices. The goal of this study is to develop a preclinical testing method for quantitatively and qualitatively evaluating the efficacy of noncompliant balloon angioplasty (NC BA) treatment in human ex vivo calcified plaque (CP). NC BA using a 3- and 4-mm diameter balloon was performed on an ex vivo tibial calcified vessel obtained from an amputation. Three-dimensional microcomputed tomography (μ-CT) imaging was performed pre- and post-BA to compare crack density in the CP. Comparing the pre- and posttreatment three-dimensional μ-CT images showed a glass-like cracking that occurred in the CP due to the BA procedure. Expansion of the 3-mm balloon showed little tissue deformation and no CP cracking. Although expansion of the 4-mm balloon occurred nonuniformly along balloon length and across the perpendicular projections, the balloon generated cracking throughout the CP, which allowed the surrounding elastic tissue to be dilated. This combined X-ray microscopy and μ-CT technique is a useful preclinical tool for quantifying the efficacy of percutaneous treatments for CP. Because of its nondestructive nature, the CP structure can be visualized pre- and posttreatment to determine the treatment effect.